(untitled) (Novos Olhares, 2012)
The following text describes how the phonographic industry initially recorded and edited the traditional Brazilian music’s acetate discs, which occurred both through non-profit institutes and recording companies. In regard to commercialization, the article identifies the strategies employed by the recorders to achieve and enlarge the potential market for that type of music.